Review of Evidence Collection and Protection Phases in Digital Forensics Process - Sonmez, Yesim Ulgen; Varol, Asaf (Şeref SAĞIROĞLU, 2017)
This study reviews crime scene investigation, collection of evidence, and protecting evidence phases of digital forensic process based on the research in the literature. Using appropriate methods for collecting and protecting electronic evidence would contribute to digital forensics and information technology law. In order to have effective evidence analysis, the first phases of the digital forensic process need to be completed through appropriate methods. In this study, the main emphasis will be on digital forensics process as well as hardware and software utilized during this procedure.